Pengaruh Jumlah Mata Sayat Flute End Milling Cutting Terhadap Kualitas Permukaan Austenite Stainless Steel (ASS) 304 - Hendra Butar Butar; Rahman Hakim; Windy Stefani; Saiful Arif; Nugroho Pratomo Ariyanto (Jurnal Teknologi dan Riset Terapan (JATRA), 2023)
The working principle of CNC Milling machine is the machine rotates and contacts with the workpiece so that erosion and cutting occur. The machining process affects the mechanical properties of the material, so it needs to conduct a study to determine changes in the character of the material due to the machining process. This research was conducted to determine the effect of the number of 2 flutes and 4 flutes on the workpiece surface roughness using PMC-5VT20 CNC Milling machine. Specimens test use 304 material stainless steel that has strength and resistance to the corrosive. The research method was carried out experimentally using 304 stainless steel material which had been done with a finishing process using an endmill cutter with 2 flutes and 4 flutes. The roughness of specimens were tested using surface roughness tester to determain the effect of flute number on the surface roughness. The result of testing shows that the number of flutes affects the roughness of the machining process. The roughness value using 2 flutes is lower than the use of 4 flutes.